Desenvolvimento, atração e retenção de capital humano em cidades de pequeno porte: o caso de Panambi/RS (Brasil) - Kepler, Roseli Cristina Hack (Universidade do Vale do Rio dos Sinos, 2025)
Human capital is one of the foundations for the development of organizations, cities and regions. Human capital is meant, the stock of available skills and knowledge, whether in individual or collective level, constituted by formal education, technical and professional education and informal education, which is tangible in qualified professionals. These professionals make choices about their place of activity and are therefore susceptible to factors of development, attraction and retention. Previous studies reveal that large cities, with qualified urban infrastructure, prevail as attraction poles of qualified professionals. Based on the theory of human capital, especially in studies on mobility, attraction and retention of human capital, this study examined the following question: How different actors, such as companies, public power, educational institutions and civil associations, act to establish development, attraction, and retention of human capital in small cities? To answer this question, the case of the city of Panambi/RS was analyzed, which meets the criterion of being a small city and that contemporary faces the challenge of developing, attracting and retaining qualified professionals, although it had economic success as an industrial pole in the twentieth century. Secondary data were consulted and 14 interviews conducted, with managers representatively of the investigated actors. The data were analyzed in its content in in the approach of thematic analysis. Three themes were considered subdivided into categories. The themes development of human capital and attraction and retention of human capital in cities derived from previous reviewed studies. Already, a third theme that consists of the actions of the QUADRUPLE propeller, was established inductively. As conclusions, it is noteworthy that this study contributes that, in small cities, the limitations caused by the weak agglomeration to the attraction and retention of human capital, can be compensated to some extent with connectivity, quality of life, health and safety. The study also contributes highlighting that the actions of the Helix Quadruple, involving companies, public authorities, educational institutions and civil associations, such as the creation of a local hub of innovation, continuous investments in education at different levels, and the improvement of health and safety services, mitigating gaps related to the development, attraction and retention of human capital in a small city.
Keywords: Educação; Capital humano; Fatores de atração e retenção; Cidades; Education; Human capital; Attraction and retention factors; Cities; ACCNPQ::Ciências Sociais Aplicadas::Administração